PTCy versus ATG as graft-versus-host disease prophylaxis in mismatched unrelated stem cell transplantation - Penack, Olaf; Abouqateb, Mouad; Peczynski, Christophe; Boreland, William; Gülbas, Zafer; Gedde-Dahl, Tobias; Castilla-Llorente, Cristina; Kröger, Nicolaus; Eder, Mathias; Rambaldi, Alessandro; Bonifazi, Francesca; Blau, Igor Wolfgang; et al. (Blood cancer journal, 2024)
There is an increased risk of GVHD and of non-relapse mortality (NRM) after allogeneic stem cell transplantations (alloSCT) when mismatched unrelated donors (MMUD) are used. In Europe, it is standard practice to use rabbit anti-thymocyte globulin (rATG) to reduce the high NRM and GVHD risks after MMUD alloSCT. As an alternative to rATG, post-transplantation Cyclophosphamide (PTCy) is in increasing clinical use. It is currently impossible to give general recommendations regarding preference for one method over another since comparative evidence from larger data sets is lacking. To improve the evidence base, we analyzed the outcome of rATG vs. PTCy prophylaxis in adult patients with hematologic malignancies undergoing first peripheral blood alloSCT from MMUD (9/10 antigen match) between Jan 2018 and June 2021 in the database of the European Society for Blood and Marrow Transplantation (EBMT). We performed multivariate analyses using the Cox proportional-hazards regression model. We included 2123 patients in the final analyses (PTCy, n = 583; rATG, n = 1540). p values and hazard ratios (HR) presented here are multivariate outcomes. Two years after alloSCT we found a lower NRM in the PTCy group of 18% vs. 24.9% in the rATG group; p = 0.028, HR 0.74. Overall survival in the PTCy cohort was higher with 65.7% vs. 55.7% in the rATG cohort; p < 0.001, HR 0.77. Progression-free survival was also better in the PTCy patients with 59.1% vs. 48.8% when using rATG; p = 0.001, 0.78. The incidences of chronic GVHD and acute GVHD were not significantly different between the groups. We found significantly lower NRM as well as higher survival in recipients of peripheral blood alloSCTs from MMUD receiving PTCy as compared to rATG. The results of the current analysis suggest an added value of PTCy as GVHD prophylaxis in MMUD alloSCT.
Gesehen am 23.08.2024